Fatalism and ICD-11 CPTSD and PTSD diagnoses: results from Nigeria, Kenya & Ghana. Issue 1 (1st January 2021) - Levin, Yafit; Bachem, Rahel; Palgi, Yuval; Hyland, Philip; Karatzias, Thanos; Shevlin, Mark; Ben-Ezra, Menachem; Maercker, Andreas
ABSTRACT: Background: Existing research on post-traumatic sequelae suggests a positive association between fatalism and symptoms of post-traumatic stress disorder (PTSD). However, the associations between fatalism and the new ICD-11 diagnosis of complex PTSD (CPTSD) have never been explored before. Objective: The current study explored the association between fatalism and PTSD and CPTSD in samples from three African countries. Methods: A total of 2, 524 participants from Nigeria ( n = 1018), Kenya ( n = 1006), and Ghana ( n = 500) completed measures of fatalism (non-judgemental fatalism, current fatalism, pessimistic fatalism, prospective fatalism) and the International Trauma Questionnaire (ITQ). A combination of a multinomial regression and path analysis was used to identify fatalism predictors of PTSD and CPTSD versus no diagnosis, and CPTSD versus PTSD, adjusted for demographic variables and trauma exposure. Results: While PTSD was not predicted by any of the fatalism types, compared to no diagnosis, CPTSD was significantly predicted by pessimistic, non-judgemental and current fatalism, both compared to no diagnosis and PTSD. Conclusions: The results broaden the knowledge on potential correlates of the new diagnosis of CPTSD. Addressing fatalistic beliefs by empowering people to think that they can choose their fate should be further explored as a possible target for intervention in the treatment of CPTSD. HIGHLIGHTS: The study explored the association between fatalism and PTSD and CPTSD according to ICD-11 definition in samples from three African countries. The results broaden the knowledge beyond Western population on potential correlates of the new diagnosis of CPTSD.